2017
DOI: 10.1371/journal.pone.0180167
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities found in placental tissues are associated with severe chorioamnionitis and adverse birth outcomes

Abstract: Preterm birth is a major cause of neonatal mortality and morbidity worldwide. Bacterial infection and the subsequent inflammatory response are recognised as an important cause of preterm birth. It is hypothesised that these organisms ascend the cervical canal, colonise placental tissues, cause chorioamnionitis and in severe cases infect amniotic fluid and the foetus. However, the presence of bacteria within the intrauterine cavity does not always precede chorioamnionitis or preterm birth. Whereas previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 44 publications
5
96
1
7
Order By: Relevance
“…Staphylococcus is a genus of bacteria commonly associated with mammalian skin and mucosal surfaces (91). It was detected in a preliminary molecular survey of the fetus and placenta of the Japanese macaque (85) and it has also been reported in numerous DNA sequence-based investigations of the human placenta (3138, 4143). However, Staphylococcus has also been identified as a background DNA contaminant in sequence-based studies (48), including in several prior studies of the human placenta (39, 57, 62).…”
Section: Discussionmentioning
confidence: 78%
“…Staphylococcus is a genus of bacteria commonly associated with mammalian skin and mucosal surfaces (91). It was detected in a preliminary molecular survey of the fetus and placenta of the Japanese macaque (85) and it has also been reported in numerous DNA sequence-based investigations of the human placenta (3138, 4143). However, Staphylococcus has also been identified as a background DNA contaminant in sequence-based studies (48), including in several prior studies of the human placenta (39, 57, 62).…”
Section: Discussionmentioning
confidence: 78%
“…Given our observations of maternal dietary influence, it is intriguing to postulate when this early life influence is occurring. We and others have previously demonstrated that we can employ metagenomics and 16S sequencing to detect and characterize a unique and low abundance, low biomass placental and neonatal microbiome (Aagaard et al, ; Amarasekara, Jayasekara, Senanayake, & Dissanayake, ; Antony et al, ; Ardissone et al, ; Bassols et al, ; Borghi et al, ; Chu et al, ; Chu et al, ; Collado, Rautava, Aakko, Isolauri, & Salminen, ; Doyle et al, ; Doyle et al, ; Gomez‐Arango et al, ; Jiménez et al, ; Leon et al, ; Martinez et al, ; Parnell et al, ; Prince et al, ; Rautava, Collado, Salminen, & Isolauri, ; Satokari, Grönroos, Laitinen, Salminen, & Isolauri, ; Zheng et al, ). Furthermore, in an elegant set of experiments, Li et al (2019) recently demonstrated that memory CD4 + T cells are generated during intrauterine development in the human fetal intestine, which are phenotypically similar to innate‐like lymphocytes previously described in mice that are dependent on microbes for their maintenance (Prince et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…11 Other studies have detected bacteria utilizing PCR assays and culture, but differ on their findings of correlation with pre-term labor and delivery. [2][3][4][5][6][7] Therefore, this study has great implications beyond correlating to infant mortality within a closed colony due to the differing and opposing previously reported results.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many published reports regarding the topic of intra-amniotic sterility; however, these reports tend to contradict one another in terms of bacteria and correlation with pre-term labor and delivery. [2][3][4][5][6][7] Our study aimed to analyze the sterility of amniotic fluid from vervet monkeys in a colony with a poor reproductive history. We hypothesized that microbial contamination would be higher in pregnancies that terminate as pre-term or stillbirth.…”
Section: Introductionmentioning
confidence: 99%